The thickness of odontoblast-like cell layer after induced by propolis extract and calcium hydroxide - Irfan Dwiandhono; Ruslan Effendy; Sri Kunarti (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2016)
Background: Propolis is a substance made from resin collected by bees (Apis mellifera) from variety of plants, mixed with its saliva and various enzymes to build a nest. Propolis has potential antimicrobial and antiinflammatory agents with some advantages over calcium hydroxide (Ca(OH)2). Ca(OH)2 has been considered as the “gold standard” of direct pulp-capping materials, but there are still some weakness of its application. First, it can induce pulp inflammation which last up to 3 months. Second, the tissue response to Ca(OH)2 is not always predictable. Third, the tunnel defect can probably formed in dentinal bridge with possible bacterial invasion in that gap. Purpose: This study was aimed to determine and compare the thickness of odontoblast-like cells layer after induced by propolis extract and Ca(OH)2 in rat’s pulp tissue. Method: Class 1 preparation was done in maxillary first molar tooth of wistar mice until the pulp opened. The Ca(OH)2 and propolis extract was applied to induce the formation of odontoblast-like cells, the cavity was filled with RMGIC. The teeth were extracted (after 14 and 28 days of induction). The samples were then processed for histological evaluation. Result: There were significant differences between the thickness of odontoblast-like cells after induced by propolis extract and Ca(OH)2. Conclusion: The propolis extract as the direct pulp capping agent produces thicker odontoblast-like cell layer compared to Ca(OH)2.